Comparative evaluation of four commercial analyzers for the serological screening of hepatitis A - Junhyup Song; Jiyeon Kim; Sinyoung Kim; Younhee Park (Virology Journal)
Abstract Background Serological assays for hepatitis A virus (HAV) play a crucial role in diagnosing acute infections and monitoring disease transmission. Given their widespread use in clinical laboratories, discrepancies among different immunoassay analyzers may have significant clinical implications. This study aimed to assess the quantitative and qualitative agreement between anti-HAV total immunoglobulin (or IgG) and IgM results across four fully automated immunoassay systems. Methods A total of 280 and 223 clinical serum samples were tested for anti-HAV total immunoglobulin (or IgG) and IgM, respectively, using four immunoanalyzers: Vitros ECiQ (Ortho), Atellica IM 1600 (Siemens), Alinity i (Abbott), and Cobas e801 (Roche). Quantitative correlations and qualitative agreements were assessed, and cases with discordant anti-HAV IgM results were further investigated using available clinical data. Results While the total immunoglobulin (or IgG) assay demonstrated a strong correlation across all platforms, substantial discrepancies were observed in the IgM results, particularly between the Vitros ECiQ and the other three analyzers. Although the other three platforms yielded concordant results, the clinical review indicated that in 4 out of 6 cases (66.6%), the Vitros ECiQ results aligned more closely with the clinical presentations. Conclusions This study highlights inter-assay variability in anti-HAV IgM detection and underscores the need for improved harmonization across platforms. Future studies incorporating a sufficient number of molecularly confirmed acute hepatitis A cases are warranted to clarify the causes of false results and minimize the potential clinical impact of inaccurate testing.